Upaya Meningkatkan Hasil Belajar Ekonomi dengan Menggunakan Media Video Pembelajaran Pada SMA Muhammadiyah 1 Palangkaraya - Suyati, Endang Sri (Anterior Jurnal, 2018)
Which has the characteristics that describe all of the information / data naturally / what it is, and the researcher as the primary instrument and attempting to solve or answer the problems encountered during the present situation. Data collection techniques in this study is testing and observation. Data analysis techniques of drawing this study using the percentage formula and individual classical completeness and N-gain formula.activity of students in cycle 1 to obtain an average score of 3.18 with both the criteria and the second cycle had a mean score average 3.75 with both criteria, thus the effort teachers to be active learners can be said to be successful. Based on the results of the study concluded that the learning outcomes of students after using the instructional video media also increased and a better understanding of the abilities active in the matter, where the initial test results in the classical percentage of 22% only 5 students who scored ≥ 75 of the 23 participants learners. The results of tests on the first cycle in the classical percentage of 69% are 16 students who scored ≥ 75 of 23 students means an increase between pre-test and the first cycle of 47%. There was an increase again in the second cycle the percentage increase in the classical learning outcomes by 100% or all students who scored ≥ 75. Means that by using the medium of video learning can improve learning activity and improving student learning outcomes in class X-3 SMA Muhammadiyah 1 Palangkaraya.